A Systematic Literature Review and Bibliometric Analysis of Refuse-Derived Fuel (RDF) as an Alternative Energy Source - Risma Mila Rosa; Devi Maulida Rahmah; Muhammad Achirul Nanda; Arief Ameir Rahman Setiawan; Ryozo Noguchi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Refuse-Derived Fuel (RDF) has increasingly been explored as an alternative energy source derived from solid waste, offering potential contributions to both energy transition and improved waste management. However, the environmental performance of RDF systems has not been widely examined using comprehensive approaches such as Life Cycle Assessment (LCA) and circular economy frameworks. This study applies a Systematic Literature Review (SLR) combined with bibliometric analysis to identify research trends and thematic developments in RDF studies. A total of 109 Scopus-indexed articles were analyzed using VOSviewer, resulting in nine thematic categories, including fuel characterization, production processes, energy recovery, environmental impact, LCA, circular economy, modeling and simulation, application, and innovation. The findings show that most studies still focus on production and energy recovery, while sustainability oriented topics such as LCA and circular economy remain relatively underexplored.